Cognitive Reappraisal and Depression in Children with a Parent History of Depression - Kudinova, Anastacia Y. (J Abnorm Child Psychol, 2018)
Although decades of research have documented that children whose parents have a history of Major Depressive Disorder (MDD) are at a higher risk of developing depression themselves, not all of these children go on to develop depression themselves, thus highlighting the need to understand potential moderators of risk. The current study examined whether child emotion regulation, specifically, the use of cognitive reappraisal and suppression, moderated the link between parent and child depression. We recruited 458 parents and their children between the ages of 7–11 from the community. The majority of children were Caucasian (74.2%) and approximately half were girls (46.1%). Among children with a parent history of MDD, those who reported using cognitive reappraisal more frequently were less likely to have a history of depressive diagnoses themselves and had higher current levels of positive affect. Although children’s use of suppression was not associated with their levels of depressive symptoms among children with a parent history of MDD, higher levels of suppression were related to higher levels of depressive symptoms among children with no parent history of MDD. These findings suggest that, among children with a history of parent depression, children’s use of cognitive reappraisal may influence their own risk for developing depression and highlights the potential utility of early interventions that focus on improving the use of emotion regulation strategies like cognitive reappraisal among children of depressed parents.